Clinical Presentation of Mild To Moderate COVID–19 Disease in Patients Admitted at Tertiary Care Hospital Pakistan - Ameer, Khalid; Rafique, Aisha; Abbas, Sana; Burki, Ahmed Mujadid Khan; Abbas, Beenish (Pakistan Armed Forces Medical Journal, 2022)
Objective: To explore the clinical presentation of mild to moderate COVID-19 disease. Study Design: Cross-sectional analytical study Place and Duration of Study: Tertiary Care Hospital, Rawalpindi from Mar 2020 to Aug 2020. Methodology: Three hundred and ninety-two patients with mild to moderate illness, PCR positive for COVID 19 were included. Frequency of typical symptoms of COVID-19 disease cough, fever, sore throat and shortness of breath and trends in laboratory assays were recorded. Discharge Criteria was two consecutive negative PCR performed upon 7th and 8th day of admission, subsequently on the 11th and 12th day if found positive previously. Results: A total of 392 patients were enrolled in the study with age range of 9-45 years. Out of 96 (24.5%) patients presented with cough and fever. Out of 112 (28.6%) patients complained of fatigue and myalgias. Chest x-ray had a bilateral patch in 96 (24.5%) patients and serum ferritin was raised in 96 (24.5%) patients. The coagulation profile was deranged in 64 (16.3%) patients. PCR results remained positive till 12th day in 80 (20.4%) patients. Conclusion: Fever, Cough and sore throat and deranged biochemical, radiological and haematological markers prove multisystem implications of mild to moderate COVID-19 disease. PCR can remain positive till the 12th day and beyond in modest disease.